2019
DOI: 10.35448/jte.v14i2.6530
|View full text |Cite
|
Sign up to set email alerts
|

PERAN PEMASARAN MEDIA SOSIAL DALAM MENCIPTAKAN KEPUTUSAN PEMBELIAN MELALUI KESADARAN MEREK (Studi pada Instagram Clothing Line Bangjo)

Abstract: ABSTRACKThe development and great effects of the internet are beginning to be understood by many people, and competitors have made many innovations and sales through the internet. Therefore social meadia marketing which is part of internet marketing was chosen as the focus of research. This study aims to determine how the influence of social media marketing on purchasing decisions through brand awareness. The independent variable studied was social media marketing (X), purchasing decision (Y) as the dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
1
5
0
5
Order By: Relevance
“…It has subsequently implications for increasing purchase decision. These results support previous research conducted by Adhawiyah, Anshori, and AS (2019). Social media marketing has an indirect effect on purchase decision through brand awareness.…”
Section: N P R E S Ssupporting
confidence: 91%
“…It has subsequently implications for increasing purchase decision. These results support previous research conducted by Adhawiyah, Anshori, and AS (2019). Social media marketing has an indirect effect on purchase decision through brand awareness.…”
Section: N P R E S Ssupporting
confidence: 91%
“…Armayani and Jatra (2019) explain that a good brand image has a positive influence on purchasing decisions and the higher the brand image created by the company, the level of consumer decision making to buy also increases. Brand image not only has a direct effect on consumer purchasing decisions but can mediate the relationship between social media marketing and purchasing decisions, where social media marketing can have a significant influence on purchasing decisions (Adhawiyah and Anshori, 2019). The use of social media marketing has an impact in shaping the brand image of Pesen Kopi and so that the Pesen Kopi strategy through social media marketing produces a positive influence.…”
Section: Discussionmentioning
confidence: 99%
“…Research on digital marketing strategies through social media, viral marketing and its influence on purchasing decisions has been carried out by many previous researchers. Several previous studies have found that promotion via social media has a significant influence on purchasing decisions [18], [22], [1], [6], [7], [2], [9]. Likewise, several previous studies have concluded that viral marketing has a significant impact on procurement decisions [6], [21], [1], [19], [8].…”
Section: Previous Studymentioning
confidence: 99%
“…Several previous studies have found that promotion via social media has a significant influence on purchasing decisions [18], [22], [1], [6], [7], [2], [9]. Likewise, several previous studies have concluded that viral marketing has a significant impact on procurement decisions [6], [21], [1], [19], [8].…”
Section: Previous Studymentioning
confidence: 99%